النمذجة الرقمية لاستقراء انهيار وصلة لحامية حلقية معرّضة لتأثير ضغط غاز بحالتي الثبات والتغير (Latakia University Journal -Engineering Sciences Series, 2019)
This research submits an analyzed study that describes the reasons of failure happened in welded joints which are subjected to effects of pressure forces of gas, that flows through carbon-steel pipe which has connection with that joints, and its induced vibration which may lead to weakening it at its special Heat Affected Zone that be considered one of the most undesirable vestiges resulting from welding procedure and previous failure had been happened through it. We had adopted numerical modeling by using program (ANSYS.14) to analyze the stresses affecting the welded joint in two distinct issues, static and dynamic pressure, which led to a set of conclusions that could be important notes to basics of a new design, can be used as a preventive procedure to limit the effect of the causes of the collapse. النمذجة الرقمية لاستقراء انهيار وصلة لحامية حلقية معرّضة لتأثير ضغط غاز بحالتي الثبات والتغير يتضمن هذا البحث دراسة تحليلية لتبيان أسباب الانهيار الحاصل في الوصلات اللحامية الخاضعة لتأثير قوى ضغط الغاز المار خلال أنبوب ترتبط به هذه الوصلات والتي ينتج عنها نوعاً من الاهتزازات  التي تؤدي بدورها إلى إجهادها في المنطقة المتأثرة حرارياً منها والتي تعتبر أحد مخلفات عملية اللحام الأكبر تأثيراً على حالة الفشل الذي تعرضت له الوصلة . تم اعتماد طريقة النمذجة الرقمية باستخدام برنامج (ANSYS.ver14) لتحليل الإجهادات المؤثرة في الوصلة بحالتي الضغط الستاتيكي والديناميكي الأمر الذي قاد إلى مجموعة من الاستنتاجات التي أُمكن من خلاها الاستدلال لأساسيات تصميم جديد يمكن استخدامه كإجراء وقائي يحد من تأثير أسباب الانهيار التي أدت إلى فشل الوصلة اللحامية السابقة .